Sikap Mahasiswa Terhadap Plagiarisme Di Institut Teknologi Padang - Nurhasanah Nurhasanah; Ardoni Ardoni (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to describe student attitudes towards plagiarism at the Padang Institute of Technology. This type of research is quantitative with descriptive methods. The population in this study was active even semester students at the Padang Institute of Technology with sampling using the Slovin formula. The number of samples was 95 students. The main instrument used was a research questionnaire which had been tested for validity and reliability. The variable in this research is student attitudes towards plagiarism. Data collection was carried out through questionnaires. Data were analyzed through stages of inspection, tabulation, and Fishbein's multiattribute attitude model. Fishbein's multi-attribute attitude model has two main components, namely beliefs and evaluation. To determine the value of beliefs and evaluation, five indicators of plagiarism are needed, namely knowledge of the act of plagiarism, acceptance of the act of plagiarism, feelings towards the act of plagiarism, direct attitude towards plagiarism (plagiarism by others). ), direct attitude towards plagiarism (plagiarism by oneself). The results of the research are that the first component, beliefs (bi) has a total score of 43.91. This indicates that the score on the beliefs component has a positive value. The second component, namely evaluation (ei) has a total score of 43.52, this indicates that the score on the evaluation component is positive. Students' attitudes towards plagiarism at the Padang Institute of Technology were declared positive, which was the result of the final calculation between the two main components of attitude according to Fishbein's multi-attribute attitude model, namely beliefs (bi) and evaluation (ei) of 136.42.